2015
DOI: 10.3390/ph8020151
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species, Apoptosis, Antimicrobial Peptides and Human Inflammatory Diseases

Abstract: Excessive free radical generation, especially reactive oxygen species (ROS) leading to oxidative stress in the biological system, has been implicated in the pathogenesis and pathological conditions associated with diverse human inflammatory diseases (HIDs). Although inflammation which is considered advantageous is a defensive mechanism in response to xenobiotics and foreign pathogen; as a result of cellular damage arising from oxidative stress, if uncontrolled, it may degenerate to chronic inflammation when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 110 publications
(159 reference statements)
1
89
1
3
Order By: Relevance
“…From the structural study, it was confirmed that plant defensins are characterized by 8 cysteine and 2 glycine at position 13 and 34 with an aromatic acid and glutamic acid in its structure. Plant defensins do not show antibacterial activity but possess antifungal activity against plants and human pathogens (Oyinloye et al 2015).…”
Section: Defensinsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the structural study, it was confirmed that plant defensins are characterized by 8 cysteine and 2 glycine at position 13 and 34 with an aromatic acid and glutamic acid in its structure. Plant defensins do not show antibacterial activity but possess antifungal activity against plants and human pathogens (Oyinloye et al 2015).…”
Section: Defensinsmentioning
confidence: 99%
“…There are about 30 cathelicidins reported from mammals. The cathelicidin (LL-37) present in the human body is known for its activity against bacteria, fungi and viruses (Oyinloye et al 2015).…”
Section: Cathelicidinsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For example, cotreatments of magainin analog, one AMP derivative and two anticancer drugs, cis-Platinum, and etoposide have shown synergistic antitumor effects, primarily due to the formation of voltagedependent ion channels that change membrane potential and functionality. 1,46 Hepcidin, composed of 20 amino acids, functions as an important regulator of intestinal iron absorption by binding to the iron exporter ferroportin, thus inhibiting iron absorption. 47 In the process of inflammation, hepcidin can be secreted by the liver and retains mammalian iron balance.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs also exhibit anticancer activity by inducing cytolytic action on tumor cells. 1,2 Hepcidin, an AMP, was originally isolated from Oreochromis mossambicus. 3 There are three hepcidin isoforms, namely hepcidin 1-5, hepcidin 2-2, After membrane attachment, such AMPs may form pores via insertion into lipid bilayers or cause membrane perturbation to disrupt intracellular pathways.…”
Section: Introductionmentioning
confidence: 99%